Anti-TNF therapy for paediatric IBD: the Scottish national experience. Issue 4 (12th February 2015) - Cameron, F L; Wilson, M L; Basheer, N; Jamison, A; McGrogan, P; Bisset, W M; Gillett, P M; Russell, R K; Wilson, D C
Abstract : Background and aims: Biological agents are being increasingly used in the UK for paediatric-onset inflammatory bowel disease (PIBD) despite limited evidence and safety concerns. We evaluated effectiveness and safety in the clinical setting, highlighting drug cost pressures, using our national Scottish PIBD biological registry. Methods: Complete usage of the biological agents, infliximab (IFX) and adalimumab (ADA) for treatment of PIBD (in those aged <18 years) from 1 January 2000 to 30 September 2010 was collated from all treatments administered within the Scottish Paediatric Gastroenterology, Hepatology and Nutrition (PGHAN) national managed service network (all regional PGHAN centres and paediatric units within their associated district general hospitals). Results: 132 children had biological therapy; 24 required both agents; 114 had Crohn's disease (CD), 16 had ulcerative colitis (UC) and 2 had IBD Unclassified (IBDU). 127 children received IFX to induce remission; 61 entered remission, 49 had partial response and 17 had no response. 72 were given maintenance IFX and 23 required dose escalation. 18 had infusion reactions and 27 had adverse events (infections/other adverse events). 29 had ADA to induce remission (28 CD and 1 UC), 24 after IFX; 10 entered remission, 12 had partial response and 7 had no response. All had maintenance; 19 required dose escalation. 12 children overall required hospitalisation due to drug toxicity. No deaths occurred with either IFX or ADA. Conclusions: Complete accrual of the Scottish nationwide 'real-life' experience demonstrates moderate effectiveness of anti tumour necrosis factor agents in severe PIBD but duration of effect is limited; significant financial issues (drug cost—need for dose escalation and/or multiple biological usage) and safety issues exist.